Safety and efficacy of cisplatin combinations with vinorelbine, paclitaxel and gemcitabine – a systematic review and meta-analysis - Islam, Inaya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.